2017
DOI: 10.1002/eap.1467
|View full text |Cite
|
Sign up to set email alerts
|

From pest data to abundance‐based risk maps combining eco‐physiological knowledge, weather, and habitat variability

Abstract: Noxious species, i.e., crop pest or invasive alien species, are major threats to both natural and managed ecosystems. Invasive pests are of special importance, and knowledge about their distribution and abundance is fundamental to minimize economic losses and prioritize management activities. Occurrence models are a common tool used to identify suitable zones and map priority areas (i.e., risk maps) for noxious species management, although they provide a simplified description of species dynamics (i.e., no ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…For example, similar results on the relationships between S. rubrovittatus abundance and landscape factors at similar spatial scales were reported in two independent regions, which were 300 km apart (Yasuda et al 2011;Takada et al 2012). Over large areas of hundreds of kilometers, previous studies have shown common patterns in the response of landscape factors and biological responses of arthropods (Gardiner et al 2009;Lacasella et al 2017;Zhang et al 2018), although there was no attempt to extrapolate using empirical validation like the current study. Therefore, the adjusted predictive model may be able to extrapolate even further from the area of current study if the environmental and biological context is similar.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, similar results on the relationships between S. rubrovittatus abundance and landscape factors at similar spatial scales were reported in two independent regions, which were 300 km apart (Yasuda et al 2011;Takada et al 2012). Over large areas of hundreds of kilometers, previous studies have shown common patterns in the response of landscape factors and biological responses of arthropods (Gardiner et al 2009;Lacasella et al 2017;Zhang et al 2018), although there was no attempt to extrapolate using empirical validation like the current study. Therefore, the adjusted predictive model may be able to extrapolate even further from the area of current study if the environmental and biological context is similar.…”
Section: Discussionsupporting
confidence: 83%
“…S6), indicating regional and other related factors, which were not dealt with in this study, affecting the model tting. (Lacasella et al 2017), which is reasonable to explain the population dynamics of poikilothermic organisms. Previous studies of rice-attacking pentatomids in Japan suggested that temperature of rice heading season and grain growing season have a positive effect on the total pecky rice damage of several pentatomid species, including S. rubrovittatus in southwestern Japan (Sugiura et al 2002) and the abundance of another mirid species T. caelestialium in northern Japan (Kawasaki et al 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Precipitation changes alter water balance, local water availability and nutrient cycling, directly affecting ecosystem productivity and food availability for primary consumers, especially in arid and semi-arid regions 52 . Precipitation changes and water stress may directly or indirectly affect eco-physiological responses of herbivores 53 and some analyses suggest that precipitation changes can have stronger effect on population dynamics 54 or species optimum elevation 55 than temperature changes alone. The effects of precipitation changes and increased drought may be even more pronounced when these changes act synergistically with temperature increases, ultimately leading to widespread tree mortality and vegetation shifts with cascading effects on animal communities and ecosystem functioning 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The trends we identify could be used to reason the protection of the crops at the landscape level. Early warning system tools based on this approach may modulate risk estimates at the plot level and thus limit the systematic use of preventive treatments 31 . As for active landscape design, the management of host plant areas seems both the most influential and the easiest aspect to handle 32 .…”
Section: ***mentioning
confidence: 99%